Theoretical and practical aspects of sedentary behavior among medical professions in the field of dentistry – part I - Liliana Moraru; Viorel Perieanu; Mihai Burlibașa; Claudia-Camelia Burcea; Mădălina Violeta Perieanu; Mădălina Adriana Malița; Irina-Adriana Beuran; Mihai David; Oana Eftene; Mihaela Chirila; Ioana-Cristina Neagoe; Magdalena Natalia Dina; et al. (Romanian Medical Journal, 2021)
Sedentary behavior, both professional, occupational, and leisure, recreational, is one of the major risk factors for cardio-metabolic health and premature mortality. But, we find this sedentary behavior in many of the existing professional activities in 2021, among which are the professional activities with a medical profile in the field of dentistry: specific activities of the dental office (and here we discuss dentists and dental nurses) and activities specific to the dental technique laboratory (in this case, we are talking about dental technicians).